2010
DOI: 10.1177/1073191110382848
|View full text |Cite
|
Sign up to set email alerts
|

The NEO Five-Factor Inventory: Latent Structure and Relationships With Dimensions of Anxiety and Depressive Disorders in a Large Clinical Sample

Abstract: The present study evaluated the latent structure of the NEO Five-Factor Inventory (NEO FFI) and relations between the five-factor model (FFM) of personality and dimensions of DSM-IV anxiety and depressive disorders (panic disorder, generalized anxiety disorder [GAD], obsessive–compulsive disorder, social phobia [SOC], major depressive disorder [MDD]) in a large sample of outpatients (N = 1,980). Exploratory structural equation modeling (ESEM) was used to show that a five-factor solution provided acceptable mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
113
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(133 citation statements)
references
References 53 publications
(121 reference statements)
17
113
2
1
Order By: Relevance
“…In three studies (Kritjansson et al, 2011;Mattsson, 2012;Meleddu et al, 2012), the CFA solution showed poor fit, whereas the ESEM showed good model fit. In five studies, the CFA models displayed poor fit and adequacy of the ESEM solutions would be dependent on the particular index focused on (Furnham et al, 2013;Marsh et al, 2009;Marsh et al, 2010;Perry et al, 2012;Rosellini & Brown, 2011). Specifically, the RMSEA indicated fit in both CFA and ESEM models, the CFI indicated a lack of fit for the CFA models and borderline fit for the ESEM models and the TLI evidenced poor fit regardless of the method used.…”
Section: Introductionmentioning
confidence: 99%
“…In three studies (Kritjansson et al, 2011;Mattsson, 2012;Meleddu et al, 2012), the CFA solution showed poor fit, whereas the ESEM showed good model fit. In five studies, the CFA models displayed poor fit and adequacy of the ESEM solutions would be dependent on the particular index focused on (Furnham et al, 2013;Marsh et al, 2009;Marsh et al, 2010;Perry et al, 2012;Rosellini & Brown, 2011). Specifically, the RMSEA indicated fit in both CFA and ESEM models, the CFI indicated a lack of fit for the CFA models and borderline fit for the ESEM models and the TLI evidenced poor fit regardless of the method used.…”
Section: Introductionmentioning
confidence: 99%
“…Out of these five personality dimensions, Extraversion and Neuroticism are predictors of anxiety and other affective/psychological disorders (12)(13)(14). Further, Conscientiousness is positively correlated with Generalized Anxiety Disorder (15). However, the one personality factor that best indicates the presence of anxiety/ depression is a low level in the Emotional Stability dimension (16).…”
Section: The Five Factor Modelmentioning
confidence: 99%
“…This scale measures the overall loneliness of an individual. The items were measured on a 6-point Likert Scale ranging from 'very strongly disagree' (1) to 'very strongly agree' (6). A high score indicates higher loneliness and a low score indicates lower loneliness.…”
Section: Lonelinessmentioning
confidence: 99%
“…Results showed significant negative correlation between extraversion and depression. Reference [6] evaluated the relationship between NEO Five-Factor Inventory, and depressive and anxiety disorders. Structural equation modelling was used and it was found out that extraversion was inversely related to major depressive disorder.…”
Section: Introductionmentioning
confidence: 99%